Application of Product Moment Correlation and Complete Linkage Clustering Methods in Analyzing the Results of the Lecturer Questionnaire - Agustian, Harliyus (SENATIK STT Adisutjipto, 2018)
The use of questionnaires is needed by a lecturer to make improvements in the implementation of the teaching process in the classroom, so that it can correct deficiencies in the teaching process that has taken place. The results of the questionnaire cannot show the variables that must be corrected by a lecturer based on the item questionnaire. So we need a grouping of data for each variable in the results of the questionnaire. The clustering approach model cannot directly group a variable into an object to be clustered. This study clustered the variables on a questionnaire with the approach of Complete Lingkage Clustering by calculating the distance of the matrix using the Product Moment Corelation to find correlations for each questionnaire variable, so the cluster results obtained were several optimal clusters with the membership of each cluster variables from the questionnaire. Clustering data for questionnaire variables can be applied properly by applying product moment correlation to calculate the distance matrix. The cluster results can show the components of the questionnaire variables that must be corrected by the lecturer.